2015
DOI: 10.13189/azb.2015.030403
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Evaluation of Botanical Extract, Bioagents and Fungicides against Purple Blotch Diseases of Bunch Onion in Bangladesh

Abstract: The experiment was carried out to survey for incidence and prevalence of purple blotch disease which ranged from 30.49 to 51.76 percent. Isolation, identification of pathogen and determination of pathogenicity were conducted as well; In-vitro evaluation of some botanical extracts, some commercial fungicides and some antagonistic microorganisms against Alternaria porri were performed. At 5 percent concentration of Adhatoda vasica extract showed the maximum of 91.11% inhibition of mycelial growth of A. porri fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 8 publications
1
9
0
1
Order By: Relevance
“…While, the minimum mycelial inhibition (66.66%) was noticed in T. koningii (Table 2 and Plate 1). Similar findings were observed by (Kumari et al, 2006) [6] (Pramodkumar, 2007) [10] , (Kareem, 2008) [5] , (Mishra and Gupta; Wanggikar, 2012) [8] and Rahman et al (2015) [11] who reported that T. viride as effective under in vitro in inhibiting the maximum mycelial growth of the fungus. Among the bacterial bioagents, Pseudomonas fluorescens-4 i.e.…”
Section: Resultssupporting
confidence: 82%
“…While, the minimum mycelial inhibition (66.66%) was noticed in T. koningii (Table 2 and Plate 1). Similar findings were observed by (Kumari et al, 2006) [6] (Pramodkumar, 2007) [10] , (Kareem, 2008) [5] , (Mishra and Gupta; Wanggikar, 2012) [8] and Rahman et al (2015) [11] who reported that T. viride as effective under in vitro in inhibiting the maximum mycelial growth of the fungus. Among the bacterial bioagents, Pseudomonas fluorescens-4 i.e.…”
Section: Resultssupporting
confidence: 82%
“…The bio-control agents-Bacillus subtilis, Pseudomonas fluorescens, Trichoderma harzianum and two isolates of Trichoderma reesei were evaluated against mycelial growth of the fungus using dual culture technique (Bhadra et al, 2014). The effect of fungicides, namely Tilt 250 EC (Propiconazole) and Amistar Top 325 SC (Azoxystrobin + Difenoconazole) on the radial growth of the fungus was determined on PDA medium using the food poison technique (Rahman et al, 2015). A requisite quantity of fungicides was added to the medium with a concentration of 250 ppm, 500 ppm, and 750 ppm.…”
Section: Efficacy Of Bio-control Agents and Fungicides Against F Solanimentioning
confidence: 99%
“…The ethanolic plant extracts were prepared from leaves of Tagetes erecta L., Azardirachta indica L., and Lowsonia innermis L. and each plant extract of different concentrations (10%, 20% and 30%) were mixed with PDA as different treatment combinations (Rahman et al, 2015). Inoculated petri-plates were kept in an incubation chamber at 25±2°C.…”
Section: Efficacy Of Bio-control Agents Plant Extracts and Fungicides Against Curvularia Lunatamentioning
confidence: 99%